Internet of (Moving) Things: Paradigms and Opportunities - Althobaiti, Ohood Saud (Nordic and Baltic Journal of Information & Communications Technologies, 2021)
The Internet of Things (IoT) is an emerging connectivity paradigm that impacts every imaginable industry. Since the IoT is applied in numerous sectors, for instance, e-health, e-learning, smart cities, virtual conferences, industrial field, the technology aims at influencing our ways of communication and how we operate in each sector. IoT is one of the innovations of significant interest in the world especially during crucial cases such as coronavirus outbreak (COVID-19). It is said that the technology will profoundly affect the behaviours of potential users and numerous aspects of daily activities. This paper aims at evaluating the IoT, and at developing a broad comprehension of the technology as well as examine it from a mobility point of view.